PENGARUH MODEL PEMBELAJARAN RADEC TERHADAP KETERAMPILAN BERPIKIR KRITIS SISWA KELAS V MATA PELAJARAN IPA MATERI BUMI BERUBAH MI NEGERI 1 TASIKMALAYA - Zakiah Dewi, Suci; Nina Hasunah (Asatidzuna | Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
The 21st century demands students to have critical thinking skills. However, the facts in the field show that students' critical thinking skills are still low. This study aims to determine the effect of the RADEC learning model on students' critical thinking skills according to the RADEC stages, namely (Read), (Answer), (Discuss), (Explain), and (Create). The RADEC model was chosen because it has been proven to be able to improve critical thinking skills through systematic stages and in accordance with student characteristics. This study uses the True Experimental design method. In this research design, two groups were randomly selected, namely the experimental group and the control group. From both groups, a pretest was given to determine students' initial abilities, then the experimental group was given treatment using the RADEC learning model, while the control group was not given treatment using the PBL learning model. The experimental group and the control group were given a posttest. This study was conducted at MI Negeri 1 Tasikmalaya, with class VA as the experimental class and class VB as the control class as the research sample. Data collection techniques and instruments used observation sheets, critical thinking test sheets in the form of multiple choice questions and questionnaires. The results showed that the average pretest value of the experimental class was 0.55 and the percentage value was 55.43%. Meanwhile, the average posttest value of the experimental class increased significantly, namely 0.73 and the percentage value was 73.26%. While in the control class, the average pretest value was 0.58 with a percentage value of 58.33%. And in the posttest of the control class, the average value increased to 0.67 and the percentage value was 67.70%. The data analysis techniques used were descriptive statistical analysis, inferential analysis, namely prerequisite tests and hypothesis tests (independent sample t test). Based on the results of the hypothesis test, a Sig (2-tailed) value of 0.049 <0.05 was obtained. Thus, it can be concluded that there is a significant influence between learning taught with the RADEC learning model on the critical thinking skills of fifth-grade students in the science subject of the changing earth material at MI Negeri 1 Tasikmalaya.